Error Analysis of Procedure Text Writing Among Sixth-Semester English Education Students at UMNU Kebumen - Rohmah, Nazma Ishmaranti; Asroriyah, Atik Muhimatun (UM Purwokerto Press, 2025)
This study analyzes the errors made by sixth-semester students at Universitas Ma’arif Nahdlatul Ulama (UMNU) Kebumen in writing English procedure texts. It aims to identify the specific linguistic challenges students face in producing clear and effective procedural writing. Employing a qualitative descriptive method, the research examined ten procedure texts written during an academic writing course. Each text was analyzed to determine the frequency and types of errors. The findings indicate that grammatical errors were the most frequent (40%), followed by syntactical errors (27%), lexical errors (18%), and coherence-related problems (15%). These results suggest that students particularly struggle with constructing grammatically accurate sentences and logically organizing ideas. The study emphasizes the importance of instructional strategies that focus on grammar, vocabulary enrichment, sentence structure, and overall text coherence. The findings are expected to inform more effective pedagogical practices and support EFL students in improving their academic writing proficiency, especially in producing functional texts such as procedures.